2002
DOI: 10.1080/13921657.2002.10512486
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyological Evaluation of Fish Passes Constructed in Lithuania

Abstract: The current paper is a survey of fish passes built in Lithuania and a generalisation of the data on their efficiency collected during the period 19981999. At the present time, there are 11 fish passes in Lithuania, two of which are fish locks, three pool and orifice fish passes, three pool and weir fish passes, one Denil fish pass and two bay-pass channels. Two fish passes are at a standstill because of some technical faults. Three fish passes operate inefficiently. According to the data collected in 1998 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Still, about 29 to 54 adults moved upstream of Finsjö during 2001 and 2002, which corresponded to increased densities of 0 þ brown trout. The densities of 0 þ brown trout upstream of Finsjö in 2002 were twice as high as the highest mean values for the downstream sites during the entire study period, a result paralleling that reported for a Lithuanian river (Ziliukas and Ziliukiene, 2002). The annual number of spawners upstream of Finsjö will probably increase in the next couple of years when individuals observed in this study, remembering their migration routes, return to spawn again.…”
Section: Efficiency Of Fishwayssupporting
confidence: 81%
“…Still, about 29 to 54 adults moved upstream of Finsjö during 2001 and 2002, which corresponded to increased densities of 0 þ brown trout. The densities of 0 þ brown trout upstream of Finsjö in 2002 were twice as high as the highest mean values for the downstream sites during the entire study period, a result paralleling that reported for a Lithuanian river (Ziliukas and Ziliukiene, 2002). The annual number of spawners upstream of Finsjö will probably increase in the next couple of years when individuals observed in this study, remembering their migration routes, return to spawn again.…”
Section: Efficiency Of Fishwayssupporting
confidence: 81%
“…For instance in the Nemunas River in Lithuania, the spawning stock of twaite shad originally ascended approximately 400 km up the Nemunas River. After the construction of the Kaunas hydroelectric dam in 1959, 224 km upstream of the mouth of the Nemunas River, the access to the upper reaches of the river was blocked (Maksimov & Toliušis, 1999;Repečka, 1999;Ž iliukas & Ž iliukien_ e 2002). Additionally, the discharge of industrial wastewater from paper mills into the lower streches of the Nemunas River and the Curonian Lagoon, and an increase in tonnage of marine shipping, including the Klaypedskiy railroad crossing, greatly impeded the migration of twaite shad and other anadromous fishes to their spawning grounds (Manyukas, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Denil fishways included those designed as a steep flume with vanes installed to dissipate the flow and decrease velocity (Clay 1995). Fish lift/lock systems collected fish in an enclosed lock and then raised the water level to the top of the dam by the addition of water (Ziliukas and Ziliukiene 2002). Trap and truck installations included some form of attraction/collection system, followed by the transportation of collected fish upstream via appropriate vehicles (Schilt 2007).…”
Section: Methodsmentioning
confidence: 99%